Determinants of Women’s Labor Force Participation in Nepal: Evidence from the Nepal Living Standards Survey Using Logistic Regression with Interaction Effects - Adhikari, Reena; Adhikari, Gyan Mani; Dhungana, Agya (Adhyayan Journal, 2026)
This paper examines the factors that determine the level of women involvement in the workforce in Nepal using Nepal Living Standards Survey IV (NLSS-IV) data on the same that was conducted in 2010/ 11 by the Central Bureau of Statistics. The analytical dataset will comprise of 8,734 women aged between 15 and 64 years sampled using a stratification, multistage cluster sampling method that covered 7420 households in 75 districts. A binary logistic regression model is modeled, which has labor-force participation (defined as participation in one or more hours of paid work seven days before survey) as the dependent variable. Individual (age, educational attainment, marital status), household (wealth quintile, household composition, female household headship) and spousal characteristics and geographic variables are covariates in the model. Hierarchical model-building approach is embraced and interaction terms are proposed to represent heterogeneity of effects. Findings indicate that the participation of working-age women in the labor force was an average of only 32.1. Every year of schooling added 6 per cent (odds ratio=1.06, 95 percent confidence interval=1.04-1.08) to the fully specified model. Married women were less likely to take part by 55 percent compared to unmarried women (OR 0.45, 95 percent CI 0.3853). Preschool children below five years of age minimized the probability of participation by 29 percent (OR = 0.71, 95 percent CI= 0.63-0.81). Females in the richest wealth quintile had 57% less odds of participating than those in the poorest wealth quintile (OR=0.43, 95% CI=0.34 0.54). Considerable interactions were found in terms of education and marital status (OR = 1.05, p = 0.002), wealth and location (OR = 0.87, p = 0.032), and spousal education and women education (OR = 0.97, p = 0.005). The results show that the participation of women in the labor force of Nepal depends on the interaction between educational attainment, marriage restrictions, family and economic situations, and geographical factors. These findings have significant implications on the policy design to be used in promoting economic participation of women in the nation.